2017
DOI: 10.1007/s10238-017-0471-4
|View full text |Cite
|
Sign up to set email alerts
|

Methylation status of IGF2 DMR and LINE1 in leukocyte DNA provides distinct clinicopathological features of gastric cancer patients

Abstract: DNA methylation of leukocyte DNA has been proposed to be a biomarker for cancer that can be used to target patients for appropriate clinical implementation. We investigated IGF2 DMR and LINE1 methylation in the leukocyte DNA and their association with clinicopathological features and prognosis of gastric cancer (GC) patients. Methylation status of IGF2 DMR and LINE1 in the leukocyte DNA was quantified using bisulfite pyrosequencing in 207 GC patients. Methylation of both IGF2 DMR and the LINE1 was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…This evidence also indicates that activation of the IGF-II locus may promote EMT [191] that could then facilitate tumor invasion and metastasis. This is consistent with reports that IGF-II is associated with progression and prognosis [193,194,195,196]. A further implication of the reactivated developmental program is related to the splice variant of the insulin receptor, IR-A, which was originally reported to be highly expressed in fetal and cancer cells [77].…”
Section: Igf-ii Locus and Cancersupporting
confidence: 89%
“…This evidence also indicates that activation of the IGF-II locus may promote EMT [191] that could then facilitate tumor invasion and metastasis. This is consistent with reports that IGF-II is associated with progression and prognosis [193,194,195,196]. A further implication of the reactivated developmental program is related to the splice variant of the insulin receptor, IR-A, which was originally reported to be highly expressed in fetal and cancer cells [77].…”
Section: Igf-ii Locus and Cancersupporting
confidence: 89%
“…If selected DNA methylation markers are consistent and replicable, they can be utilized in clinical practices. Since blood is a convenient tissue in noninvasive cancer assays, evaluation of cancer biomarker is under intensive attention in DNA extracted from WBC [21].…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka Tomokazu and colleagues found that low expression of Trefoil factor 1 (TFF1) was relevant to poor survival in gastric cancer patients who were treated by surgery alone, while the expression of TFF1 was silenced by DNA methylation and was also associated with tumor invasion [31]. Other studies also showed that high methylation status of IGF2 and LINE1 was associated with invasion of gastric cancer [32] and hypermethylation of GFRA3 promoter may predict poor overall survival in gastric cancer patients who underwent surgery [33]. Besides, Li et al reported that integrative analysis of DNA methylation and gene expression identified a six epigenetic driver signature for predicting prognosis in hepatocellular carcinoma [34].…”
Section: Discussionmentioning
confidence: 99%